Magnetically driven outflows in the 3D common envelope evolution of massive stars - Vetter, Marco; Röpke, Friedrich; Schneider, Fabian; Pakmor, Rüdiger; Ohlmann, Sebastian; Morán Fraile, Javier; Lau, Mike Y. M.; Leidi, Giovanni; Gagnier, Damien; Andrássy, Róbert (Astronomy and astrophysics, 2025)
Recent three-dimensional magnetohydrodynamical simulations of the common envelope interaction have revealed the self-consistent formation of bipolar magnetically driven outflows. These outflows are launched from a toroidal structure that has properties of a circumbinary disk. So far, the dynamical impact of bipolar outflows on the common envelope phase remained uncertain, and we aim to quantify its importance in this work. Due to the large computational expense of such simulations, we focus on a specific setup to illustrate the impact on common envelope evolution by comparing two simulations – one with magnetic fields and one without. We used the three-dimensional moving-mesh hydrodynamics code AREPO to perform simulations, focusing on the specific case of a 10 M⊙ red supergiant star with a 5 M⊙ black hole companion. We find that by the end of the magnetohydrodynamic simulations (after ∼1220 orbits of the core binary system), about 6.4% of the envelope mass is ejected through the outflow and contributes to extracting angular momentum from the disk structure and core binary. Given the increased torques induced by the launched material near the core binary, the simulation shows a reduction of the final orbital separation by about 24% compared to the purely hydrodynamical scenario, while the envelope ejection rate exhibits only temporary differences and is dominated by recombination-driven equatorial winds. We further investigated the magnetic field amplification and the launching mechanism of the bipolar outflows. The results are consistent with previous works: The magnetic fields are primarily amplified by strong shear flows and the magnetically driven outflows are launched by a magneto-centrifugal mechanism. The outflows are additionally supported by local shock heating and strong magnetic gradients and originate from a distance of 1.1 times the core binary’s orbital separation from its center of mass. From this and preceding works, we conclude that the magnetically driven outflows and their role in the common envelope phase are a universal aspect of such dynamical interactions and we further discuss possible implementations in analytical and non-magnetic numerical model approaches. We propose an adaptation of the αCE formalism for common envelope interactions, that accounts for magnetic effects, by modifying the final orbital energy with a factor of 1 + Mout/μ, with Mout as the mass ejected through the bipolar outflows and μ as the reduced mass of the core binary.